Influence of Angle κ and Higher-Order Aberrations on Visual Quality Employing Two Diffractive Trifocal IOLs - Cecilio Velasco-Barona; Claudia Corredor-Ortega; Alejandra Mendez-Leon; Nadia L. Casillas-Chavarín; Daniel Valdepeña-López Velarde; Guadalupe Cervantes-Coste; Daniel Malacara-Hernández; Roberto Gonzalez-Salinas (Journal of Ophthalmology)
Prospective, randomized, comparative, and controlled study to estimate the association between angle κ distance and higher-order aberrations (HOAs) with postoperative visual acuity after presbyopia-correcting IOL implantation. Forty-three eyes from 43 patients were included and randomly assigned in two groups for either AT LISA tri 839MP or Acrysof IQ PanOptix IOL implantation. The OPD-Scan III analyzer was utilized to assess the angle κ distance and higher-order aberration (HOAs). Twenty-three eyes were in the Acrysof IQ PanOptix group and 20 patients in the AT LISA tri 839MP group. The uncorrected distance visual acuity (UDVA) for the PanOptix group was 0.092 ± 0.10, whereas for AT LISA tri was 0.050 ± 0.06 (P=0.229). The uncorrected intermediate visual acuity (UIVA) for the PanOptix group was 0.173 ± 0.18, whereas for AT LISA tri, it was 0.182 ± 0.11 (P=0.669). Uncorrected near visual acuity (UNVA) was 0.068 ± 0.04 and 0.085 ± 0.07, respectively (P=0.221). Also, correlation coefficient between HOAs and the Strehl ratio for each group were −0.768 (P<0.0001) and −0.863 (P=0.0001). Patients implanted with both trifocal IOLs showed excellent postoperative visual performance at all distances at the six-month follow-up visit. No association was found between angle κ distance and postoperative visual acuity regardless of the angle κ magnitude or the two trifocal IOLs inner optical diameter. Also, internal aberrations demonstrated a significant inverse correlation with the Strehl ratio for both trifocal IOLs.